A study of the mechanism on preventive action towards family members from involved in drug addiction at Taman Pelangi Ledang / Mohd Khairul Hafiz Ismail - Ismail, Mohd Khairul Hafiz (Faculty of Administrative Science and Policy Studies, 2011)
Mechanism means by which an effect is produced or a purpose is accomplished. Preventive action is an action to eliminate the cause of a potential nonconformity or other undesirable potential situation. In the family members involvement in drug addicts is a group of persons who form a household under one head, including parents, children and relative which one of them are involved in drugs addict. The main objective of this study is to identify the mechanism on preventive action towards family members which involved in drug addiction at Taman Pelangi Ledang, Johor. The researcher also want to determine the family reaction towards the drug addiction measure and to identify the action on drug addiction in family institution. Besides that researcher want to analyze the relationship of the variables between the dependent variable and independent variable as well as to analyze the reaction and action towards family members which involved in drug addiction in family institution.